Relatos de experiência do ensino remoto para Olimpíadas de Matemática - Sena, Mônica da Silva Morais (2021)
This work presents specific training for mathematics competitions, such as the Kangaroo Mathematics Brazil Competition, the Mathematics Olympiad in Public Schools (OBMEP) and the Rio Grande do Norte State Mathematics Olympiad (OMRN). The training is directed at high school students and was applied with students from the Escola Estadual Antonia Guedes Martins, located in the city of Lagoa D’Anta, Rio ˆ Grande do Norte. It consists in developing the students ability to solve olympic mathematical problems, through the practice of solving the problems found in the tests of the aforementioned competitions. Initially, we formulated the application of the training in person, however, due to the Sars-CoV2 pandemic, it was adapted to be worked with students remotely. For this, the weekly meetings, which would be in person, became synchronous, being carried out through the Google Meet application, the students also watched lives of problem solving on Instagram and made simulations online. Besides that, students who did not participate in synchronous meetings have the opportunity to access them asynchronously on the YouTube platform.